Oxygen-ether-bridged perylene diimide dimers: Efficient synthesis, properties, and photovoltaic performance. (September 2020) - Wang, Helin; Chen, Lingcheng; Xiao, Yi
Abstract: The research of non-conjugated organic semiconductor materials with excellent photoelectric properties can promote the development of new materials in the field of material science. Herein, we developed three new oxygen-ether-bridged perylene diimide (PDI) dimers, namely bo -2PDI, oo -2PDI, and bb -2PDI, which were synthesized by coupling reactions with a moderate yield. Owing to the different ether-bridged positions, three PDI dimers exhibit different photophysical and electrochemical properties. Thus, three PDI dimers show strong absorption from 400 to 600 nm, suitable energy levels, and high electron mobilities, which implies that three PDI dimers can be used as the electron acceptors for non-fullerene organic solar cells (OSC). By using PTB7-Th as the donor and three PDI dimers to fabricate the inverted OSCs, the optimal power conversion efficiency ( PCE ) of 3.06% was obtained for the bb -2PDI-based OSC without any additive. This PCE value was higher than those of bo -2PDI (1.47%) and oo -2PDI (1.24%). Our advances show that oxygen-ether-bridged PDI dimers are promising high-efficiency electron acceptors for non-fullerene OSCs. Graphical abstract: Image 1 Highlights: Three oxygen-ether-bridged dimers were developed by the coupling reaction. Three PDI dimers exhibit different photophysical and electrochemical properties. Three PDI dimers show suitable LUMO levels and high electron mobility. The bb -2PDI-based OSCs show superior photovoltaic performance than others.